PI3K: An Attractive Candidate for the Central Integration of Metabolism and Reproduction - Acosta-Martinez, Maricedes (Frontiers in Endocrinology, 2012)
In neurons, as in a variety of other cell types, the enzyme phosphatidylinositol-3-kinase (PI3K) is a key intermediate that is common to the signaling pathways of a number of peripheral metabolic cues, including insulin and leptin, which are well known to regulate both metabolic and reproductive functions. In this article, I explore the possibility that PI3K is a key integrator of metabolic and neural signals regulating gonadotropin releasing hormone (GnRH)/luteinizing hormone (LH) release and explore the hypothesis that this enzyme is pivotal in many disorders where gonadotropin release is at risk. Although the mechanisms mediating the influence of metabolism and nutrition on fertility are currently unclear, the strong association between metabolic disorders and infertility is undeniable. For example, women suffering from anorectic disorders experience amenorrhea as a consequence of malnutrition-induced impairment of LH release, and at the other extreme, obesity is also commonly co-morbid with menstrual dysfunction and infertility. Impaired hypothalamic insulin and leptin receptor signaling is thought to be at the core of reproductive disorders associated with metabolic dysfunction. While low levels of leptin and insulin characterize states of negative energy balance, prolonged nutrient excess is associated with insulin and leptin resistance. Metabolic models known to alter GnRH/LH release such as diabetes, diet-induced obesity, and caloric restriction are also accompanied by impairment of PI3K signaling in insulin and leptin sensitive tissues including the hypothalamus. However, a clear link between this signaling pathway and the control of GnRH release by peripheral metabolic cues has not been established. Investigating the role of the signaling pathways shared by metabolic cues that are critical for a normal reproductive state can help identify possible targets in the treatment of metabolic and reproductive disorders such as Polycystic Ovarian Syndrome (PCOS).